212k views
3 votes
F (x) = 2x^2 - 4x + 1​

2 Answers

3 votes

Answer: x = √(((-F - 4)^2)/16 - 1/2) + (F + 4)/4 or x = (F + 4)/4 - √(((-F - 4)^2)/16 - 1/2)

Step-by-step explanation:

Solve for x:

F x = 2 x^2 - 4 x + 1

Subtract 2 x^2 - 4 x + 1 from both sides:

-2 x^2 + F x + 4 x - 1 = 0

Collect in terms of x:

-1 + x (F + 4) - 2 x^2 = 0

Divide both sides by -2:

1/2 + 1/2 x (-F - 4) + x^2 = 0

Subtract 1/2 from both sides:

1/2 x (-F - 4) + x^2 = -1/2

Add 1/16 (-F - 4)^2 to both sides:

1/16 (-F - 4)^2 + 1/2 x (-F - 4) + x^2 = 1/16 (-F - 4)^2 - 1/2

Write the left hand side as a square:

(1/4 (-F - 4) + x)^2 = 1/16 (-F - 4)^2 - 1/2

Take the square root of both sides:

1/4 (-F - 4) + x = √(1/16 (-F - 4)^2 - 1/2) or 1/4 (-F - 4) + x = -√(1/16 (-F - 4)^2 - 1/2)

Subtract 1/4 (-F - 4) from both sides:

x = √(((-F - 4)^2)/16 - 1/2) + (F + 4)/4 or 1/4 (-F - 4) + x = -√(1/16 (-F - 4)^2 - 1/2)

Subtract 1/4 (-F - 4) from both sides:

Answer: x = √(((-F - 4)^2)/16 - 1/2) + (F + 4)/4 or x = (F + 4)/4 - √(((-F - 4)^2)/16 - 1/2)

User Donesha
by
4.9k points
2 votes

i don't know specifically what you are looking for but:

Direction: Opens Up

Vertex: (1, -1)

Axis of Symmetry: x = 1

and i attached the graph

F (x) = 2x^2 - 4x + 1​-example-1
User Xaelis
by
4.7k points